Open bone augmentation for large osseous defects in chronic, recurrent glenohumeral instability - Tengku Mohamed Shihabudin, Tengku Muzaffar; Sharifudin, Mohd Ariff; Mohamed Muslim, Darhaysham Al Jefri (2012)
Introduction: The glenohumeral joint is one with the greatest mobility and intimate contact between the articular surfaces of the humeral head and glenoid labrum contributes to its stability. Patients with recurrent dislocations have bone deficits in one or both of these surfaces, due to the presence of a Bankart lesion or an engaging Hill-Sachs lesion. Although successful arthroscopic management of instability associated with osseous defects is an alternative, open reconstruction is often indicated. Large osseous defects can be challenging and preclude arthroscopic treatment. Case Report: A 30-year-old man with a history of chronic, recurrent left shoulder dislocation for more than 10 years was referred to us for further evaluation and treatment. Our assessment revealed a large Bankart lesion combined with a large Hill Sach lesion over the humeral head. Open reduction with bone augmentation of the glenoid osseous defect was performed using autogenous bone graft from the iliac crest. Intraoperative assessment showed adequate stability for the humeral head defect without the need for intervention. The technical aspect of the surgery is described together with the clinical outcomes of the patient. Discussion/Conclusion: An estimated osseous defect with a width of 20% of the glenoid length remains unstable and requires bone augmentation. Bone grafting was the stabilizing mechanism in the restoration of the glenoid concavity. Most patients with bone deficits on both articular surfaces can suitably be treated by reconstructing only one of the deficits, but occasionally both defects may require intervention. To date, there are no validated preoperative guidelines for cases when both procedures are required. An intra-operative assessment remains our best tool.